Materiality and formal possibilities in religious buildings of the 20th century. The Ronchamp Chapel and the Cathedral of Brasilia - Villamón, Juan (2024)
Religious buildings are the manifestations that people have built to express their faith. Over time, they leave behind works that show us their beliefs and values regarding the knowledge of a higher being. In these buildings we can analyze their meaning, the references they use for their design development and how they are materialized. We chose as examples from the 20th century Le Corbusier with the Ronchamp chapel and Oscar Niemeyer with the Brasilia cathedral, both made of reinforced concrete. Each one, in their own way, reveals their thoughts (not necessarily religious) regarding faith, peace and contemplation.